AN INVESTIGATION INTO LOSS AND GAIN IN THE TRANSLATION OF A COMIC “THE ADVENTURES OF TINTIN: TINTIN IN AMERICA” INTO VIETNAMESE VERSION “NHỮNG CUỘC PHIÊU LƯU CỦA TINTIN: TINTIN TRÊN ĐẤT MỸ” - Lê Thị Nhung (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study clarified the loss and gain in the translation strategies of the comic “The adventures of tintin: Tintin in America” into Vietnamese version. The investigation indicated kinds the loss and gain of translation applied in the comic. The discussion began by collecting the data both the English version and Vietnamese version to be read and to find some Vietnamese there are ain in the translation process of the comic. The results of the investigation indicate that there are 134 patterns of loss and gain in the comic by using semantic strategies. The study also shows the finding of loss and gain in the comic as well as some reasons why the translator did the loss and gain process in translating the comic “The Adventures of Tintin: Tintin in America” into “Những chuyến phiêu lưu của Tintin: Tintin trên đất Mỹ”. Finally, the study gives some implications and recommendations have been conducted in the field of commic reading in the context of global English and of the emergence of so many variations of English so far. Through the results of this study, the researcher hopes that the result of this study can give some benefits to the translators and learners to enlarge knowledge about loss and gain and to learn how to make a good analysis, especially in translation analysis